Pengaruh Media Komik dan Poster pada Penyuluhan Gizi terhadap Pengetahuan Gizi Seimbang Anak Panti Asuhan - Khartini Kaluku; Martha Puspita Sari; Mahmud Mahmud (Jurnal Kesehatan Terpadu (Integrated Health Journal), 2023)
Multiple nutritional issues are currently facing school-age children, namely undernutrition and overnutrition induced by poor awareness of healthy nutrition guidelines. The research objective was to assess the effectiveness of the use of comic book media on the healthy nutritional awareness of children relative to poster media. This research style is a quasi-experimental design with a control pre-post examination. The research site, conducted in October 2020, was located in 2 orphanages in Ambon Region. The subjects were orphanage children with an age span of 7-17 years, with a total of 60 individuals. In healthy nutrition therapy. Children's awareness was assessed by a questionnaire at the beginning of the research. On the second day of the study, care was provided in the form of healthy nutrition therapy, divided into two classes, namely the comic group and the poster group. The paired sample t-test and separate t-test samples were used for data analysis. The findings showed that the creation of healthy nutrition awareness in the intervention and control group study subjects caused a substantial difference in the comic and poster media (p<0.05). There is a significant effect of increasing knowledge of balanced nutrition in orphanage children before and after being given comics and poster media.